Determinants of E-Learning Acceptance in Indonesia Post-COVID-19 and Its Impact on Students’ Technopreneurship - Fetria Eka Yudiana; Sari Famularsih; Alfin Rosyidha (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to address the gaps in country-specific e-learning studies by examining the key factors influencing e-learning adoption in Indonesia. Grounded in a comprehensive literature review on flow theory, service quality, and technology acceptance models, the study develops a research model that includes four independent variables (instructor characteristics, teaching materials, content design, and enjoyment), two belief variables (perceived usefulness and perceived ease of use), and one dependent variable (intention to use e-learning). Method: Data were collected from 404 respondents, comprising students and lecturers at state Islamic universities in Indonesia, using convenience sampling. The study employed SEM-PLS for data analysis, validating the research instrument's reliability and validity. Results: The results offer insights into the managerial implications and suggest directions for future research in e-learning adoption. Its results confirm six hypotheses. Novelty: This study fills a gap in e-learning adoption research by focusing on Indonesia and integrating flow theory, service quality, and technology acceptance models. It highlights the roles of perceived playfulness, ease of use, and instructional content design in influencing e-learning adoption while challenging the expected impact of instructor characteristics. This research provides fresh insights into technology-driven learning in the context of developing countries.